Case report: A rare cause of intestinal perforation in a third-trimester pregnant woman - Stiegler, Clemens; Kapitza, Christopher; Weber, Florian; Patalakh, Wladimir; Schäfer, Claus (Frontiers in Medicine, 2024)
Background: An acute abdomen is an emergency that requires accurate diagnosis and prompt treatment. In pregnancy, this process is even more challenging and sometimes the radiological findings are unclear due to the enlarged uterus displacing other structures. Moreover, endometriosis-related complications are rare and the disease often remains undiagnosed.Case presentation: We report a case of acute perforation of the cecum and the appendix during pregnancy (35 weeks of gestation) due to a previously unknown, deep infiltrating endometriosis with focal ulceration of the affected bowel wall, which presented like an acute appendicitis sonographically.Conclusions: Despite the relatively low risk, clinicians should be aware of possible endometriosisassociated complications in pregnancy with potentially life-threatening events, even in previously unknown endometriosis. Further studies should evaluate intestinal complications during pregnancy in relation to previous treatment of intestinal endometriosis (conservative vs. surgical).